Agronomic Management and Fungicide Effects on Oat Yield and Quality. Issue 3 (1st May 2015) - Mourtzinis, Spyridon; Conley, Shawn P.; Gaska, John M.
ABSTRACT: Oat ( Avena sativa L.) is an important crop in the U.S. The primary uses for oat in Wisconsin are for establishing alfalfa ( Medicago sativa L.) underseedings, livestock forage, grain, and straw production, and for human nutrition. Therefore, the quantitative and qualitative characteristics of oat are of great importance. The objective of this study was to detect the effects of variety, seeding rate, seed treatment, and foliar fungicide on total grain yield, groat proportion, test weight, plant height, lodging severity, and β‐glucan content using data from two separate trials which were established from 2011 to 2013 at the University of Wisconsin Arlington Agricultural Research Station. The results from the two 3‐yr studies highlight the importance of selecting an appropriate oat variety with superior yield and quality characteristics. The use of a high seeding rate had no effect on any of the examined characteristics. However, treated seeds with Rancona Crest exhibited increased groat yield compared to untreated seeds by 187 kg ha −1 . An important finding of this study is that the use of a foliar fungicide increased total and groat yields, and reduced lodging severity without impacting β‐glucan content. The results of this study indicate that the use of a superior variety such as 'Badger' and 'BetaGene', use of Rancona Crest seed treatment, and use of Headline foliar fungicide can increase oat yields in Wisconsin without reducing the crops' quality characteristics.